Impact of minimum wage on labour market institutions in developing countries: a systematic review / Nurul Syamira Ab Manan Iskandar and Suriyani Muhamad - Ab Manan Iskandar, Nurul Syamira; Muhamad, Suriyani (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Minimum wages have become one of the most contentious economic interventions by the government. Minimum wages compress the wage structure and alter income distribution, primarily among wage earners. Since minimum wage policies are being implemented in most developing countries, it is essential to understand their effects to determine their efficacy. The minimum wage is not a new phenomenon that has inspired numerous relevant academic studies. Minimum wage systems should complement and strengthen other social and employment policies. However, few systematic reviews of the existing literature on the effect of minimum wage in developing nations have been conducted. The purpose of this article is to underline a comprehensive literature review on the impact of minimum wage on labour market institutions in developing countries. This study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) review method, utilising the Scopus and Web of Science journal databases. The search efforts resulted in a total of 22 articles that can be systematically analysed. Most importantly, the review identified four major themes: policymakers, firm management, poverty reduction, and low-wage workers. Overall, additional analysis of the four themes led to the identification of sixteen subthemes. Several recommendations are made regarding conducting further qualitative studies, using a specific and standard systematic review method to guide research in the context of minimum wages, and implementing complementary searching techniques.